Effect of baclofen upon monosynaptic and tonic vibration reflexes in patients with spasticity - McLellan, D. L. (1973)
Measurements of monosynaptic reflex activity were made in 10 patients with spasticity before and during treatment with baclofen. There was evidence of both central sensory facilitation and increased fusimotor drive in untreated patients compared with controls. During treatment with baclofen, the central facilitation was reduced but there was no evidence of a reduction in fusimotor drive. The torque developed by vibration of the belly of the biceps and triceps muscles was not significantly different in 14 patients with spasticity compared with controls, and was not altered by treatment with baclofen despite clinical improvement in 12 of the patients. It is suggested that baclofen reduces the excitability of the monosynaptic reflex arc from dynamic spindles but does not affect the mechanisms responsible for the tonic vibration reflex.